Low profile carrier copper foil and method of making same

CN122879775APending Publication Date: 2026-10-09ANHUI HUAWEI COPPER FOIL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611393458.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0008]本申请的目的在于提供一种低轮廓载体铜箔及其制备方法,以至少在一定程度上解决低轮廓导电层难以同时兼顾载体侧剥离稳定性、表面耐热防氧化性以及树脂结合可靠性的问题

Benefits of technology

[0024]从低轮廓和精细线路加工角度看,本申请通过成分分布和界面化学改善结合可靠性,而不是主要依靠大幅增加表面粗糙度来获得机械咬合,因此有利于维持较低的Rz。并且,导电功能层整体仍以铜为主,可减小过量合金元素对导电性和常规铜蚀刻行为的不利影响;沿厚度方向呈阶梯式变化的镍/锌分布还可减少组成突变界面处的内应力集中和局部微电池效应,有利于降低精细线路加工时的边缘不齐、局部残留和缺陷风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879775A_ABST
    Figure CN122879775A_ABST
Patent Text Reader

Abstract

This application relates to the field of copper foil preparation technology, providing a low-profile carrier copper foil and its preparation method. The copper foil includes a carrier layer, a release layer, a first passivation layer, an alkali copper layer, an acid copper layer, a low-profile roughening layer, a curing layer, a second passivation layer, and a silane layer. The alkali copper layer and the acid copper layer constitute the first and second functional regions of the conductive functional layer, respectively. The average mass percentage of copper in the first functional region is higher than that in the second functional region, and the sum of the average mass percentages of nickel and zinc in the second functional region is higher than that in the first functional region. The first passivation layer and the alkali copper layer stabilize the release side interface and isolate the acidic deposition environment. The acid copper layer undertakes thickening and outer interface construction. The low-profile roughening layer, the curing layer, the second passivation layer, and the silane layer improve heat resistance, oxidation resistance, and resin bonding performance, thereby achieving a balance between controllable release, low profile, and reliable bonding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of copper foil preparation technology, and in particular to a low-profile carrier copper foil and its preparation method. Background Technology

[0002] Carrier copper foil, also known as carrier-supported ultrathin copper foil or peelable copper foil, typically consists of a carrier layer providing mechanical support and an ultrathin conductive layer that can be retained during subsequent lamination or circuit processing. Because the ultrathin conductive layer is very thin, it is prone to wrinkling, breakage, or localized defects during production, transportation, lamination, and circuit processing. Therefore, using a carrier layer to temporarily support the ultrathin conductive layer is a commonly used material solution in high-end copper foil, high-density interconnect (HDI) boards, packaging substrates, and high-frequency, high-speed circuit materials.

[0003] As electronic products evolve towards high-frequency, high-speed, miniaturized, and high-density wiring, the requirements for conductor surface roughness in circuit materials are gradually increasing. Excessive conductor surface roughness can easily increase high-frequency signal transmission loss and adversely affect the etching consistency of fine circuits. Therefore, low-profile carrier copper foil is gradually becoming an important development direction in the industry.

[0004] However, for low-profile carrier copper foil, the conductive layer near the carrier needs to maintain sufficient bonding stability before production, transportation, and lamination, and needs to be easily peeled off from the carrier after lamination or subsequent processing; the conductive layer far from the carrier needs to form a reliable bond with the heat-resistant and anti-oxidation layer, the silane layer, and the resin substrate. If the conductive layer surface is significantly roughened to improve resin adhesion, the low-profile advantage will be weakened; if the roughening treatment is reduced to decrease surface profile, the heat resistance and anti-oxidation ability of the conductive layer surface and the reliability of bonding with the resin substrate may be insufficient.

[0005] In related technologies, release performance is typically adjusted by setting a release layer or intermediate layer between the carrier layer and the ultra-thin copper layer, and subsequent bonding performance is improved by setting an anti-rust layer, heat-resistant layer, silane layer, or roughening layer on the surface of the ultra-thin copper layer. While this approach can meet the needs of conventional products to some extent, it still has the following shortcomings for low-profile, high-reliability, and fine-line processing scenarios: First, the release-side performance and resin bonding-side performance rely on independent adjustment of different layers, lacking a synergistic design for the ultra-thin conductive layer itself; second, if the ultra-thin conductive layer still uses ordinary pure copper, its surface heat resistance and oxidation resistance, as well as its bonding foundation with the surface treatment layer, are limited; third, simply increasing the strength of the surface treatment layer may introduce problems such as difficult release, interface residue, conductive layer defects, or decreased etching uniformity.

[0006] Therefore, in low-profile carrier copper foil, how to coordinate the controllable peeling requirements of the ultra-thin conductive layer close to the carrier side with the requirements of heat resistance, oxidation prevention and resin bonding far from the carrier side without relying on high roughening treatment is a technical problem that still needs to be further solved in this field.

[0007] Furthermore, in the composite preparation process of carrier copper foil, different deposition environments have different effects on interface stability, deposition efficiency, and adaptability of the outer surface treatment. If the process is not adapted separately for the carrier-side sensitive interface and the outer functional interface, problems such as disturbance of the peeling interface, increased defects in the conductive layer deposition, insufficient bonding of the surface treatment layer, or a decrease in the low profile advantage can easily occur. Summary of the Invention

[0008] The purpose of this application is to provide a low-profile carrier copper foil and its preparation method, so as to at least partially solve the problem that low-profile conductive layers are difficult to simultaneously achieve carrier-side peeling stability, surface heat resistance and oxidation resistance, and resin bonding reliability.

[0009] According to one aspect of this application, a low-profile carrier copper foil is provided. The low-profile carrier copper foil includes a carrier layer and, sequentially disposed along the rough or smooth side of the carrier layer, a release layer, a first passivation layer, an alkaline copper layer, an acid copper layer, a low-profile roughening layer, a curing layer, a second passivation layer, and a silane layer. The alkaline copper layer constitutes a first functional region of the conductive functional layer, and the acid copper layer constitutes a second functional region of the conductive functional layer; the conductive functional layer is a copper alloy layer primarily composed of copper and containing nickel and zinc. When elemental concentration analysis is performed along the thickness direction of the conductive functional layer, the average mass percentage of copper in the first functional region is higher than the average mass percentage of copper in the second functional region, and the sum of the average mass percentages of nickel and zinc in the second functional region is higher than the sum of the average mass percentages of nickel and zinc in the first functional region. The low-profile roughening layer, the curing layer, and the second passivation layer together constitute a heat-resistant and oxidation-resistant layer located between the conductive functional layer and the silane layer. In another embodiment, a carrier-side anti-oxidation / passivation layer may be provided between the carrier layer and the release layer to inhibit oxidation of the carrier layer before the release layer is formed.

[0010] In one embodiment, the mass percentage of copper in the conductive functional layer is greater than the sum of the mass percentages of nickel and zinc. Therefore, the conductive functional layer retains the fundamental properties of copper as a conductive layer in a circuit, and will not significantly deviate from the conductive properties of copper and the properties of subsequent etching processes due to the introduction of alloying elements.

[0011] In one embodiment, the thickness of the conductive functional layer is 1.5 μm to 8 μm, preferably 1.5 μm, 3 μm, or 5 μm. This thickness range allows the conductive functional layer to have sufficient continuity and meets the requirements of fine circuit processing; if the thickness is too low, it is not conducive to the formation of continuous deposition on the release layer side, while if the thickness is too high, it may reduce the processing advantages of the ultra-thin conductive layer.

[0012] In one embodiment, the thickness of the first functional region accounts for 19% to 80% of the thickness of the conductive functional layer, and the thickness of the second functional region accounts for 20% to 81% of the thickness of the conductive functional layer, and the sum of their thickness percentages is 100%. This avoids insufficient deposition continuity on the release layer side due to an excessively thin first functional region, and also avoids insufficient surface heat resistance, oxidation prevention, and bonding improvement due to an excessively thin second functional region.

[0013] In one embodiment, the content of at least one element, nickel and zinc, in the second functional region increases in a stepwise manner from the side closer to the release layer to the side closer to the heat-resistant and anti-oxidation layer. This allows for segmental control of the nickel and zinc content along the thickness direction, while maintaining the overall continuity of the conductive functional layer.

[0014] In one embodiment, the heat-resistant and anti-oxidation layer contains at least one of nickel and zinc, and the heat-resistant and anti-oxidation layer is in direct contact with the second functional region of the conductive functional layer. The surface of the second functional region may form an oxidized or hydroxide-state transition region in situ during heat-resistant and anti-oxidation treatment, drying, hot pressing, or thermal aging. This transition region is not an externally added independent physical layer, but rather an interface region formed after a chemical change occurs on the surface of the second functional region. Therefore, a more stable bonding interface can be formed between the surface of the conductive functional layer and the heat-resistant and anti-oxidation layer.

[0015] In one embodiment, the release layer includes a phosphorus-containing layer. Further, the release layer includes a first release sub-layer and a second release sub-layer, the first release sub-layer being formed by hypophosphite treatment, and the second release sub-layer being formed on the side of the first release sub-layer away from the carrier layer, and the second release sub-layer containing phosphorus and at least one metallic element selected from nickel, zinc, chromium, iron, molybdenum, cobalt, and tungsten. A first passivation layer is disposed on the side of the release layer away from the carrier layer, the first passivation layer serving to stabilize the surface state of the release layer and as a receiving interface for subsequent alkali copper initiation deposition.

[0016] In another embodiment, the release layer may further include at least one of a carbon-based physical isolation layer, a nitrogen-containing organic passivation layer, a silicon-containing passivation layer, and a boron-containing barrier layer. These optional systems can be used to adjust the interfacial energy, thermal diffusion barrier capability, or low-shear release characteristics of the release interface.

[0017] In one embodiment, the stripping layer, the first passivation layer, or the treatment solution forming both may further contain an organic salt-type interface modifier. The organic salt-type interface modifier may be selected from at least one of organic carboxylates, organic sulfonates, organic phosphates, organic phosphonates, amino acid salts, nitrogen-containing heterocyclic organic salts, and quaternary ammonium salts. The organic carboxylates may include acetates, citrates, tartrates, gluconates, lactates, or iminodiacetic acids; the organic sulfonates may include methanesulfonates, alkyl sulfonates, alkylbenzene sulfonates, or naphthalene sulfonates; the organic phosphates or organic phosphonates may include alkyl phosphates, hydroxyethylidene diphosphonates, or aminotrimethylene phosphonates; and the nitrogen-containing heterocyclic organic salts may include imidazole salts, triazole salts, or pyridine salts.

[0018] The aforementioned organic salt-type interface modifiers can be in the form of sodium salts, potassium salts, ammonium salts, or organic amine salts, and can be used alone or in combination with hypophosphite and at least one metal salt selected from nickel, zinc, chromium, iron, molybdenum, cobalt, and tungsten. Organic salt-type interface modifiers can adjust the interfacial bonding state between the release layer and the first passivation layer, and between the first passivation layer and the alkali copper layer, through complexation, surface adsorption, wetting regulation, or alteration of the initial deposition nucleation state; they do not require all components to be co-deposited as metallic components, nor do they require the formation of independently distinguishable continuous layers.

[0019] According to another aspect of this application, a method for preparing a low-profile carrier copper foil is provided. The method includes: providing a carrier layer having a rough side and a smooth side; forming a release layer on the rough side or smooth side of the carrier layer; forming a first passivation layer on the side of the release layer away from the carrier layer; performing a first-stage electrodeposition using an alkaline copper deposition system on the side of the first passivation layer away from the carrier layer to form an alkaline copper layer and a first functional region; performing a second-stage electrodeposition using an acidic copper deposition system on the side of the alkaline copper layer away from the carrier layer to form an acidic copper layer and a second functional region, such that the alkaline copper layer and the acidic copper layer together constitute a conductive functional layer; sequentially forming a low-profile roughening layer, a curing layer, and a second passivation layer on the side of the acidic copper layer away from the carrier layer; and forming a silane layer on the side of the second passivation layer away from the carrier layer.

[0020] The technical solution of this application has at least the following beneficial effects: The continuous layered structure of this application arranges the release layer, the first passivation layer, the alkali copper layer, the acid copper layer, the low profile roughening layer, the curing treatment layer, the second passivation layer, and the silane layer in sequence. The first passivation layer is used to stabilize the interface state of the release layer on the side away from the carrier layer; the alkali copper layer constitutes the first functional region near the release layer, used to form a continuous copper-based initial deposition and isolate the subsequent acidic copper deposition environment; the acid copper layer constitutes the second functional region, used to support the thickening of the conductive layer and establish the bonding basis for the outer surface treatment; the low profile roughening layer, the curing treatment layer, the second passivation layer, and the silane layer together improve the heat resistance, oxidation prevention, and interface bonding reliability of the resin bonding side.

[0021] From the perspective of materials thermodynamics and interface chemistry, copper is prone to surface oxidation in high-temperature oxygen-containing environments, and the surface active sites on the low-profile pure copper surface that can participate in stabilizing silane coupling are limited. After nickel and zinc are relatively enriched on the surface of the conductive functional layer, they are more likely to form oxidized or hydroxide species in subsequent heat-resistant anti-oxidation treatments or hot-pressing environments. These species have good interfacial continuity with the copper substrate and can serve as the film-forming basis for the heat-resistant anti-oxidation layer, thereby reducing the channels for oxygen to continue to diffuse into the copper substrate during hot pressing or thermal aging, and reducing the deepening of surface oxidation of the conductive functional layer.

[0022] From the perspective of silane coupling mechanism, the silanol groups generated after the hydrolysis of the silane coupling agent can condense with the hydroxyl groups on the surface of metal oxides or hydroxides to form MO-Si type linkages, where M can be at least one of copper, nickel, or zinc. The organic functional groups such as amino, epoxy, vinyl, or thiol groups at the other end of the silane molecule can then react, entangle, or be compatible with the resin substrate. Therefore, the relative enrichment of nickel and zinc in the second functional region and the application of a heat-resistant and anti-oxidation layer thereon can improve the interfacial force transfer capability between the silane layer and the metal and resin sides without relying on significant roughening morphology.

[0023] From the perspective of peel stability, while uniformly increasing the nickel and zinc content throughout the conductive functional layer may improve surface heat resistance, it also simultaneously increases the non-copper element content near the release layer. This can easily alter the interfacial bonding state, electrodeposition morphology, and internal stress distribution between the release layer and the conductive functional layer, causing the peel strength to deviate from the target range. In contrast, this application maintains a higher copper content in the first functional region, allowing the release layer to primarily control the peel interface, while distributing more of the nickel and zinc required for improving heat resistance, oxidation prevention, and resin bonding in the second functional region. This creates a division of labor between the peel side and the resin bonding side.

[0024] From the perspective of low profile and fine circuit processing, this application improves bonding reliability through compositional distribution and interfacial chemistry, rather than relying primarily on significantly increasing surface roughness to achieve mechanical interlocking, thus helping to maintain a low Rz. Furthermore, the conductive functional layer is still predominantly copper, which reduces the adverse effects of excessive alloying elements on conductivity and conventional copper etching behavior. The stepped nickel / zinc distribution along the thickness direction also reduces internal stress concentration and local micro-cell effects at abrupt compositional interfaces, which helps to reduce the risk of edge irregularities, local residues, and defects during fine circuit processing. Attached Figure Description

[0025] The above and other features and advantages of this application will become more apparent from a detailed description of exemplary embodiments thereof with reference to the accompanying drawings.

[0026] Figure 1This is a first set of schematic diagrams illustrating the formation process of a low-profile carrier copper foil layered structure in one embodiment of this application, used to show steps 1 to 3, namely carrier copper foil, formation of a release layer and formation of a first passivation layer.

[0027] Figure 2 This is a second set of schematic diagrams illustrating the formation process of a low-profile carrier copper foil layered structure in one embodiment of this application, used to show steps 4 to 6, namely forming an alkaline copper layer, forming an acid copper layer, and forming a low-profile roughening layer.

[0028] Figure 3 This is a third set of schematic diagrams illustrating the formation process of a low-profile carrier copper foil layered structure in one embodiment of this application, used to show steps 7 to 9, namely forming a curing layer, forming a second passivation layer, and forming a silane layer.

[0029] Figure 4 This is a schematic flowchart of a method for preparing low-profile carrier copper foil in one embodiment of this application.

[0030] Figure 5 These are images of the appearance of both sides of the CCF18+3μm (18μm is the thickness of the carrier layer, and 3μm is the thickness of the conductive functional layer) low profile carrier copper foil sample obtained in Example 1.

[0031] Figure 6 This is a low-magnification scanning electron microscope image of the sample obtained in Example 1 after the copper surface was peeled off.

[0032] Figure 7 This is a high-magnification scanning electron microscope image of the sample obtained in Example 1 after peeling off the copper surface.

[0033] Figure 8 This is a low-magnification scanning electron microscope image of the first observation area of ​​the copper rough surface of the sample obtained in Example 1.

[0034] Figure 9 This is a high-magnification scanning electron microscope image of the first observation area of ​​the copper rough surface of the sample obtained in Example 1.

[0035] Figure 10 This is a low-magnification scanning electron microscope image of the second observation area of ​​the copper rough surface of the sample obtained in Example 1.

[0036] Figure 11 This is a high-magnification scanning electron microscope image of the second observation area of ​​the copper rough surface of the sample obtained in Example 1.

[0037] Figure 12 This is a scanning electron microscope image of the first observation area of ​​the sample cross-section obtained in Example 1.

[0038] Figure 13This is a scanning electron microscope image of the second observation area of ​​the sample cross-section obtained in Example 1.

[0039] Figure 14 This is a scanning electron microscope image of the third observation area of ​​the sample cross-section obtained in Example 1.

[0040] Figure 15 This is a scanning electron microscope image of the fourth observation area of ​​the sample cross-section obtained in Example 1.

[0041] Figure 16 This is a scanning electron microscope (SEM) image showing the height of the coarsened protrusions in the cross-section of the sample obtained in Example 1.

[0042] Figure 17 This is a low-magnification scanning electron microscope image of the sample substrate surface obtained in Example 1.

[0043] Figure 18 This is a high-magnification scanning electron microscope image of the sample substrate surface obtained in Example 1.

[0044] Figure 19 This is an electron backscatter diffraction (EBSD) grain size diagram of the sample obtained in Example 1.

[0045] Figure 20 These are the inverse pole figure (IPF), grain boundary (GB), and band contrast (BC) diagrams of the sample obtained in Example 1.

[0046] The annotations for the main components in the diagram are explained below: 1. Carrier layer; 11. Carrier copper foil rough surface; 12. Carrier copper foil smooth surface; 2. Release layer; 3. First passivation layer; 4. Alkali copper layer / first functional area; 5. Acid copper layer / second functional area; 6. Low profile roughening layer; 7. Curing treatment layer; 8. Second passivation layer; 9. Silane layer. Detailed Implementation

[0047] Exemplary embodiments will now be described more fully with reference to the accompanying drawings. However, these exemplary embodiments can be implemented in many forms and should not be construed as limited to the embodiments set forth herein; rather, they are provided so that this application will be thorough and complete, and will fully convey the concept of the exemplary embodiments to those skilled in the art. The same reference numerals in the drawings denote the same or similar structures, and therefore their detailed description will be omitted.

[0048] like Figures 1 to 3As shown, one embodiment provides a low-profile carrier copper foil. The low-profile carrier copper foil includes a carrier layer 1, and a release layer 2, a first passivation layer 3, an alkaline copper layer 4, an acid copper layer 5, a low-profile roughening layer 6, a curing layer 7, a second passivation layer 8, and a silane layer 9 sequentially disposed along the rough surface 11 side or the smooth surface 12 side of the carrier layer 1. The alkaline copper layer 4 and the acid copper layer 5 together constitute a conductive functional layer, wherein the alkaline copper layer 4 constitutes a first functional region, and the acid copper layer 5 constitutes a second functional region; the low-profile roughening layer 6, the curing layer 7, and the second passivation layer 8 together constitute a heat-resistant and anti-oxidation layer.

[0049] The carrier layer 1 provides mechanical support before the production, winding, transportation, lamination, or circuit processing of the carrier copper foil. The carrier layer 1 can be electrolytic copper foil, rolled copper foil, or other metal foil that meets the requirements for continuous production and release support. In one embodiment, the carrier layer 1 is an electrolytic copper foil and has a rough surface 11 and a smooth surface 12; the release layer 2 can be formed on the rough surface 11 side or on the smooth surface 12 side. The thickness of the carrier layer 1 can be 9 μm to 70 μm, preferably 12 μm to 35 μm.

[0050] In an optional embodiment, a carrier-side anti-oxidation / passivation layer may be provided between the carrier layer 1 and the release layer 2. The carrier-side anti-oxidation / passivation layer may be a chemical conversion film, a passivation film, or a thin plating layer, and may contain at least one of chromium, zinc, nickel, and phosphorus, to inhibit surface oxidation of the carrier layer 1 before the formation of the release layer 2. This optional layer does not change... Figures 1 to 3 The order of importance among the peeling layer 2, the first passivation layer 3, the alkali copper layer 4, and the acid copper layer 5 is shown.

[0051] The release layer 2 is disposed on the rough surface 11 side or the smooth surface 12 side of the carrier layer 1, and is used to establish a controllable release base between the carrier layer 1 and the subsequently formed alkali copper layer 4. The release layer 2 may include a phosphorus-containing layer. In one embodiment, the release layer 2 includes a first release sub-layer and a second release sub-layer. The first release sub-layer is formed by hypophosphite treatment, and the second release sub-layer is formed on the side of the first release sub-layer away from the carrier layer 1, and the second release sub-layer contains phosphorus and at least one metallic element selected from nickel, zinc, chromium, iron, molybdenum, cobalt, and tungsten.

[0052] In one embodiment, the release layer 2 can be formed using a stepwise surface treatment method. For example, a first brush coating treatment can be performed on the rough surface 11 or smooth surface 12 side of the carrier layer 1 using hypophosphite to form a first release layer; subsequently, a second brush plating treatment can be performed on the side of the first release layer away from the carrier layer 1 using a second brush plating solution containing metal ions to form a second release layer. Both the first brush coating treatment and the second brush plating treatment can be carried out continuously online. After the release layer 2 is formed, a passivation treatment is performed on the side away from the carrier layer 1 to form a first passivation layer 3. The first passivation layer 3 is used to stabilize the surface state of the release layer 2 and to receive the initial deposition of the alkali copper layer 4.

[0053] In another embodiment, the release layer 2 may further include a carbon-based physical isolation layer, a nitrogen-containing organic passivation layer, a silicon-containing passivation layer, or a boron-containing barrier layer. These optional systems can be used to adjust the interfacial energy, thermal diffusion barrier capability, or low-shear release characteristics of the release interface.

[0054] Organic salt-type interface modifiers may be added to the peeling layer 2, the first passivation layer 3, or the treatment solution forming both. These organic salt-type interface modifiers may be organic carboxylates, organic sulfonates, organic phosphates, organic phosphonates, amino acid salts, nitrogen-containing heterocyclic organic salts, or quaternary ammonium salts. These organic salts can complex copper, nickel, or zinc ions, adsorb onto the copper surface, or improve the wetting state of the treatment solution, thereby adjusting the interfacial bonding force of the peeling layer 2, the uniformity of the first passivation layer 3, and the initial nucleation state of the alkali copper layer 4.

[0055] Organic carboxylates may be selected from acetates, citrates, tartrates, gluconates, lactates, or iminodiacetes; organic sulfonates may be selected from methanesulfonates, alkyl sulfonates, alkylbenzene sulfonates, or naphthalene sulfonates; organic phosphates or organophosphonates may be selected from alkyl phosphates, hydroxyethylidene diphosphonates, or aminotrimethylene phosphonates; nitrogen-containing heterocyclic organic salts may be selected from imidazole salts, triazole salts, or pyridine salts. The above salts may be in the form of sodium, potassium, ammonium, or organic amine salts, and may be used in combination with hypophosphites and at least one metal salt selected from nickel, zinc, chromium, iron, molybdenum, cobalt, and tungsten.

[0056] The aforementioned organic salt-type interface conditioning components can be located in the first exfoliation layer, the second exfoliation layer, or the first passivation layer 3. Alternatively, they can play a role in complexation, adsorption, wetting, or nucleation regulation only during the formation of the corresponding layers, without being an independently detectable essential component in the final layer structure. Their type and amount can be selected based on the target exfoliation strength, surface continuity, and subsequent alkali copper deposition morphology.

[0057] An alkaline copper layer 4 is disposed on the side of the first passivation layer 3 away from the carrier layer 1, and an acid copper layer 5 is disposed on the side of the alkaline copper layer 4 away from the carrier layer 1. The alkaline copper layer 4 and the acid copper layer 5 together constitute a conductive functional layer. The alkaline copper layer 4 forms a first functional region close to the release layer 2, and the acid copper layer 5 forms a second functional region away from the release layer 2. The conductive functional layer can serve as part or all of the circuit conductor after subsequent lamination, carrier removal, and circuit processing.

[0058] Along the thickness direction of the conductive functional layer, a first functional region is formed near the release layer 2, and a second functional region is formed near the heat-resistant and anti-oxidation layer. The average mass percentage of copper in the first functional region is higher than that in the second functional region, and the sum of the average mass percentages of nickel and zinc in the second functional region is higher than that in the first functional region. In one embodiment, this relationship can be defined as the sum of the average mass percentages of nickel and zinc in the second functional region being more than 1.2 times that of the sum of the average mass percentages of nickel and zinc in the first functional region. Therefore, the conductive functional layer is more conducive to forming a continuous and stable copper-based deposition layer on the side near the release layer 2, and more conducive to enhancing compatibility with the interface between the surface treatment layer and the resin on the side near the heat-resistant and anti-oxidation layer.

[0059] The aforementioned thickness distribution can be understood as forming two interconnected functional regions within the same conductive functional layer. The first functional region has a higher copper content and is formed by or mainly by an alkaline copper deposition system. Its electrochemical deposition behavior is more suitable as a copper-based transition zone between the release layer 2 and the subsequent acidic copper deposition environment. It is easier to form a continuous, dense, and low-defect copper-based deposition layer on the surface of the release layer 2, and the release interface is mainly regulated by the release layer 2, rather than by the direct action of the acidic plating solution on the release layer 2 or by strong or uneven bonding caused by excessive nickel or zinc.

[0060] The second functional region has a high average mass percentage of nickel and zinc, and is formed by or primarily of an acidic copper deposition system. Its function is not to replace the conductivity of copper, but rather to thicken the outer side of the conductive layer and alter the interfacial chemical state of the conductive layer's surface. Nickel and zinc are more likely to form stable oxidized or hydroxide-state surface species in subsequent heat-resistant and oxidation-resistant treatments or hot-pressing environments. These surface species can serve as the bonding basis for the heat-resistant and oxidation-resistant layer and provide more condensation-prone surface active sites for the silane layer 9.

[0061] Since the second functional region is located on the side away from the release layer 2, even though the second functional region improves the bonding reliability with the heat-resistant and anti-oxidation layer, the silane layer 9, and the resin substrate, it will not directly cause excessive enhancement of the release interface on the release layer 2 side. Therefore, this application can simultaneously satisfy the two opposing interface requirements of controllable release on the carrier side and reliable bonding on the resin side.

[0062] In one embodiment, the thickness of the conductive functional layer is 1.5 μm to 8 μm, preferably 1.5 μm, 3 μm, or 5 μm. In one embodiment, the mass percentage of copper in the conductive functional layer is greater than the sum of the mass percentages of nickel and zinc. Further, the average mass percentage of copper in the first functional region can be 90% to 99.9%, the average mass percentage of copper in the second functional region can be 80% to 99.5%, and the sum of the average mass percentages of nickel and zinc in the second functional region can be more than 1.2 times the sum of the average mass percentages of nickel and zinc in the first functional region; the specific ranges and multiples mentioned above can be selected according to actual product specifications and test data.

[0063] In one embodiment, the surface roughness Rz of at least one of the following surfaces is 0.3 μm to 3.0 μm: the surface of the silane layer 9 away from the carrier layer 1; and the surface of the conductive functional layer exposed after the carrier layer 1 is peeled off. The surface roughness Rz is measured using a white light interferometer; at least five non-overlapping regions are selected at equal intervals in the transverse direction of the sample, with an evaluation length of not less than 1 mm for each region, and the measurements are taken under the same filtering and cutoff wavelength conditions, with the arithmetic mean of the measurements for each region used as the evaluation result.

[0064] To facilitate the determination of the composition of the first and second functional regions, glow discharge optical emission spectroscopy (GDOES) was used to analyze elemental concentrations along the thickness direction of the conductive functional layer. Detection was performed from the side of the release layer 2 towards the outside of the acid copper layer 5. The first-stage deposition thickness range corresponding to the alkali copper layer 4 was designated as the first functional region, and the second-stage deposition thickness range corresponding to the acid copper layer 5 was designated as the second functional region. The Cu, Ni, and Zn concentration curves calibrated with standard samples were integrated to calculate the average mass percentage content of Cu, Ni, and Zn in each functional region. X-ray photoelectron spectroscopy depth profiling, secondary ion mass spectrometry, or cross-sectional energy dispersive X-ray spectroscopy calibrated with standard samples can be used to assist in verifying elemental distribution trends; however, the average mass percentage contents listed in the above embodiments and Table 2 are based on GDOES results.

[0065] As a detection and verification method, after peeling off the carrier layer 1, GDOES was used to perform depth profiling from the peeling layer 2 side towards the outside of the acid copper layer 5, according to uniform sample processing conditions and analytical parameters. The integration intervals of the first and second functional regions correspond to the measured thickness intervals of the alkali copper layer 4 and the acid copper layer 5, respectively. The Cu, Ni, and Zn concentration curves calibrated with standard samples were integrated to calculate the average mass percentage content of copper, nickel, and zinc in each functional region. If there is a discrepancy between the auxiliary detection results and the GDOES results, the GDOES results were used as the basis for composition determination.

[0066] In one embodiment, the content of at least one element, nickel and zinc, in the conductive functional layer increases in a stepwise manner from the side closer to the release layer 2 to the side closer to the heat-resistant and anti-oxidation layer. This structure can be formed by segmentally adjusting the supply of nickel and zinc ions, current density, or pulse parameters of the second-stage electrodeposition.

[0067] A low-profile roughening layer 6 is disposed on the side of the acid copper layer 5 away from the carrier layer 1. A curing treatment layer 7 is disposed on the side of the low-profile roughening layer 6 away from the carrier layer 1. A second passivation layer 8 is disposed on the side of the curing treatment layer 7 away from the carrier layer 1. Together, these three layers constitute a heat-resistant and oxidation-resistant layer. The low-profile roughening layer 6 is used to form a controlled low-profile bonding morphology. The curing treatment layer 7 is used to stabilize the bonding state of the roughened protrusions or particles. The second passivation layer 8 is used to improve the heat resistance and oxidation resistance of the outer surface. The acid copper layer 5 can be in direct contact with the low-profile roughening layer 6 and can form an oxidized or hydroxide-treated transition region on its surface.

[0068] The silane layer 9 is disposed on the side of the second passivation layer 8 away from the carrier layer 1, and is used to improve the interfacial bonding between the carrier copper foil and the subsequent insulating substrate. The silane layer 9 may be formed of a silane coupling agent containing at least one functional group selected from amino, epoxy, vinyl, and mercapto groups.

[0069] like Figure 4 As shown, one embodiment also provides a method for preparing a low-profile carrier copper foil. The preparation method includes: S1, providing a carrier layer 1 having a textured side and a smooth side; S2, a peeling layer 2 is formed on the rough side 11 or the smooth side 12 of the carrier layer 1; S3, a first passivation layer 3 is formed on the side of the peeling layer 2 away from the carrier layer 1; S4, an alkaline copper deposition system is used to form an alkaline copper layer 4 and a first functional area; S5, an acidic copper deposition system is used to form an acidic copper layer 5 and a second functional area; S6, a low profile roughening layer 6 is formed on the side of the copper acid layer 5 away from the carrier layer 1; S7, a curing layer 7 is formed on the side of the low profile roughening layer 6 away from the carrier layer 1; S8, a second passivation layer 8 is formed on the side of the cured layer 7 away from the carrier layer 1; S9, a silane layer 9 is formed on the side of the second passivation layer 8 away from the carrier layer 1.

[0070] like Figures 1 to 3As shown, in the process of forming a specific layered structure, a carrier layer 1 with a rough surface 11 and a smooth surface 12 can be provided first; in this embodiment, a release layer 2 is formed on the side of the rough surface 11; a first passivation layer 3 is formed on the side of the release layer 2 away from the carrier layer 1; an alkali copper layer 4 and an acid copper layer 5 are formed sequentially on the side of the first passivation layer 3 away from the carrier layer 1, wherein the alkali copper layer 4 corresponds to the first functional region and the acid copper layer 5 corresponds to the second functional region; subsequently, a low profile roughening layer 6, a curing treatment layer 7, a second passivation layer 8 and a silane layer 9 are formed sequentially on the side of the acid copper layer 5 away from the carrier layer 1.

[0071] To achieve the aforementioned compositional differences, the relative concentrations of copper, nickel, and zinc ions in the alkaline and acidic copper deposition solutions can be altered, as can deposition conditions such as current density, pulse parameters, belt speed, or temperature. In one embodiment, the alkaline copper deposition solution may contain a copper complex system and may further contain effective components that passivate, protect, or stabilize the interface of the first passivation layer 3 and the stripping layer 2; the acidic copper deposition solution can be used to improve the deposition efficiency and thickness stability of the acidic copper layer 5 and can also help increase the relative content of nickel and zinc in the second functional region.

[0072] For the online-generated electrolytic carrier layer 1, the copper surface immediately after leaving the electrolytic generation process typically exhibits high surface activity. If it remains in air or an uncontrolled environment for an extended period, non-uniform oxidation, adsorption contamination, or differences in micro-regional electrochemical states may occur, thus affecting the uniformity of the release layer 2. When necessary, an anti-oxidation / passivation layer can be formed between carrier layer 1 and release layer 2 on the carrier side; alternatively, the consistency of the carrier surface state can be maintained by shortening the time window between the formation of carrier layer 1 and the formation of release layer 2.

[0073] This preparation approach conforms to the general principles of electrodeposition and co-deposition. The local composition of the electrodeposited layer is influenced by the concentration of metal ions, complexation state, cathode potential, current density, pulse duty cycle, temperature, and mass transfer conditions in the electrodeposition solution. By employing copper-dominant deposition conditions with relatively low nickel / zinc ion ratios in the first stage, a first functional region with a high copper content can be preferentially formed. By increasing the relative supply of nickel and / or zinc ions in the second stage, or by changing the pulse parameters, belt speed, and current density, the proportion of nickel and / or zinc introduced into subsequent deposition layers can be increased, thereby forming a second functional region.

[0074] In one specific preparation method, the first-stage electrodeposition solution is an alkaline copper electrodeposition solution, which may contain copper ions, a complexing agent, and optionally nickel ions and / or zinc ions, wherein, based on metal ions, the concentration of copper ions is greater than the total concentration of nickel and zinc ions; the second-stage electrodeposition solution is an acidic copper electrodeposition solution, in which the total concentration of nickel and zinc ions is increased relative to that of the first-stage electrodeposition solution. The temperatures for the first and second-stage electrodepositions can be between 20°C and 60°C, and the current density, pulse parameters, and tape speed can be adjusted according to the target thickness, surface profile, and Ni / Zn content distribution.

[0075] The heat-resistant and anti-oxidation layer can be formed by immersion, spraying, brushing, electroplating, or chemical conversion. The treatment solution for the heat-resistant and anti-oxidation layer may contain nickel salts, zinc salts, chromium salts, phosphates, molybdates, or combinations thereof; after treatment, it can be washed with water and dried to form a thin layer containing metallic, oxidized, or hydroxide species. The silane layer 9 can be formed by treatment with a 0.01% to 5% by mass silane coupling agent solution, followed by drying at 60°C to 180°C, causing the silane layer 9 to condense or adsorb onto the surface of the heat-resistant and anti-oxidation layer.

[0076] When using pulsed electrodeposition, the pulsed current phase facilitates the reduction and deposition of metal ions, while the intermittent phase promotes the recovery of the diffusion layer and ion redistribution, thus reducing compositional fluctuations caused by local concentration polarization. During the thickness increase of the deposition area, segmented adjustments to the supply of nickel and zinc ions, current density, or pulse parameters can increase the nickel and / or zinc content of subsequent deposition portions relative to earlier deposition portions, resulting in a step-like compositional change along the thickness direction. This method can achieve compositional differences between the first and second functional regions without introducing complex equipment structures.

[0077] In one embodiment, the conductive functional layer is mainly based on the Cu-Ni-Zn system, without potassium or rare earth elements as essential components. In the aqueous electrodeposition system, potassium mainly exists in ionic form and is usually not used as a stable co-deposition component in metallic alloys; rare earth salts can be added to the electrodeposition solution as grain refining aids as needed.

[0078] The following preparation examples, comparative examples, and performance data are used to illustrate the technical solutions and effects of this application and should not be construed as limiting the scope of protection of this application.

[0079] Preparation Example 1 An electrolytic copper foil with a thickness of 18 μm is provided as a carrier layer 1, which has a rough surface 11 and a smooth surface 12. In this embodiment, the rough surface 11 is selected as the functional layer forming surface. After being cleaned with deionized water, the carrier layer 1 is activated with 1% by mass dilute sulfuric acid at 25°C for 10 seconds, and then cleaned with deionized water to reduce surface oxides and adsorbed contaminants.

[0080] A first brush coating treatment is performed on a predetermined surface of the carrier layer 1. The first brush coating treatment solution includes 8 g / L sodium hypophosphite, 5 g / L sodium citrate, and 2 g / L sodium gluconate. The pH is adjusted to 5.0±0.3 with dilute sulfuric acid or sodium hydroxide. The treatment temperature is 25±2℃, and the treatment time is 10 s. No external current is applied to form a first release layer. Subsequently, a second brush plating treatment is performed. The second brush plating treatment solution includes 2.0 g / L nickel sulfate hexahydrate, 1.0 g / L zinc sulfate heptahydrate, 5.0 g / L sodium hypophosphite, and 8.0 g / L sodium citrate. The pH is 5.2±0.3, the temperature is 25±2℃, the cathode current density is 0.2 A / dm², and the treatment time is 8 s to form a second release layer. The first and second release layers together constitute the release layer 2.

[0081] A first passivation treatment is performed on the side of the stripping layer 2 away from the carrier layer 1. The first passivation treatment solution includes 1.0 g / L sodium gluconate, 2.0 g / L sodium citrate, and 0.05 g / L sodium benzotriazole, with a pH of 7.5±0.3, a temperature of 30±2℃, and a treatment time of 10 s, forming a first passivation layer 3. Subsequently, a first-stage electrodeposition is performed: an alkaline copper deposition solution includes 65 g / L copper pyrophosphate, 280 g / L potassium pyrophosphate, 12 g / L sodium citrate, 0.30 g / L nickel sulfate hexahydrate, and 0.60 g / L zinc sulfate heptahydrate, with a pH of 8.9±0.2, a temperature of 50±2℃, a cathode current density of 1.5 A / dm², and a deposition time of 120 s, forming an alkaline copper layer 4 with a thickness of approximately 0.6 μm.

[0082] A second-stage electrodeposition was performed on the side of the alkali copper layer 4 furthest from the carrier layer 1. The acidic copper deposition solution consisted of 200 g / L copper sulfate pentahydrate, 55 g / L sulfuric acid, 1.2 g / L nickel sulfate hexahydrate, 2.0 g / L zinc sulfate heptahydrate, and 40 mg / L chloride ions. The temperature was 28 ± 2 °C, the cathode current density was 4.0 A / dm², and the deposition time was 170 s, forming an acidic copper layer 5 with a thickness of approximately 2.4 μm. The alkali copper layer 4 and the acidic copper layer 5 together constituted a conductive functional layer with a thickness of approximately 3.0 μm. GDOES depth profiling and integral conversion of the thickness intervals corresponding to the alkali copper layer 4 and the acidic copper layer 5 showed that the average mass fractions of Cu, Ni, and Zn in the alkali copper layer 4 were 99.4%, 0.2%, and 0.4%, respectively, while the average mass fractions of Cu, Ni, and Zn in the acidic copper layer 5 were 98.6%, 0.5%, and 0.9%, respectively.

[0083] A low-profile roughening layer 6 is formed on the side of the copper acid layer 5 away from the carrier layer 1: the roughening solution includes 30 g / L copper sulfate pentahydrate and 60 g / L sulfuric acid, the temperature is 25±2℃, the cathode current density is 1.2 A / dm², and the treatment time is 5 s; then a curing layer 7 is formed: the curing solution includes 80 g / L copper sulfate pentahydrate and 80 g / L sulfuric acid, the temperature is 25±2℃, the cathode current density is 2.0 A / dm², and the treatment time is 8 s; then a treatment solution including 5 g / L zinc sulfate heptahydrate, 2 g / L nickel sulfate hexahydrate, and 1 g / L sodium molybdate, with a pH of 8.5±0.3, is used, and the mixture is treated at 30±2℃ for 10 s to form a second passivation layer 8. Finally, the mixture is treated with a 0.5% (w / w) aminosilane coupling agent aqueous solution for 20 s and dried at 110℃ for 60 s to form a silane layer 9.

[0084] A low-profile roughening layer 6, a curing layer 7, and a second passivation layer 8 are sequentially formed on the side of the acid copper layer 5 away from the carrier layer 1. A silane layer 9 is then formed on the side of the second passivation layer 8 away from the carrier layer 1, resulting in a low-profile carrier copper foil. This carrier copper foil can be hot-pressed onto an insulating substrate, after which the carrier layer 1 can be peeled off.

[0085] Morphological and tissue characterization of preparation example 1 The sample obtained in Example 1 corresponds to the CCF 18+3μm specification, wherein the thickness of the carrier layer 1 is 18μm, and the alkali copper layer 4 and the acid copper layer 5 together constitute a conductive functional layer with a thickness of approximately 3.0μm; this specification corresponds to the model of the test sample, as... Figures 5 to 20 The morphology and tissue analysis of the sample are shown.

[0086] The samples obtained in Preparation Example 1 were subjected to scanning electron microscopy (SEM) and electron backscattering diffraction (ESD) analysis. SEM analysis was performed according to JY / T 0584-2020 "General Rules for Scanning Electron Microscopy Analysis Methods," using a thermal field emission electron gun with an accelerating voltage of 5kV–15kV and a magnification of 3000x–5000x. ESD analysis was performed according to GB / T19501-2013 "General Rules for Microbeam Analysis - Electron Backscattering Diffraction Analysis Methods."

[0087] like Figure 5 As shown, the CCF18+3μm low profile carrier copper foil sample obtained in Example 1 has a relatively flat appearance on both sides, which can be used to visually demonstrate the macroscopic appearance of the two sides of the sample. Figure 5 It is only used as an auxiliary image of the macroscopic state of the sample surface and is not used as a quantitative basis for roughness, peel strength or heat resistance and oxidation resistance.

[0088] like Figure 6 and Figure 7As shown, the stripped copper surface of the sample obtained in Example 1 exhibits a relatively uniform microstructure at both low and high magnification. Figure 8 and Figure 9 As shown, the first observation area of ​​the peeled copper rough surface of the sample obtained in Example 1 exhibits a low-profile coarsening morphology at both low and high magnification; as Figure 10 and Figure 11 As shown, the second observation area of ​​the peeled copper rough surface of the sample obtained in Example 1 exhibits a low-profile coarsening morphology under both low and high magnification. The above scanning electron microscope images can be used to further illustrate the uniformity of the sample surface morphology and the distribution of the coarsening protrusions.

[0089] like Figures 12 to 15 As shown, multiple cross-sectional observation areas of the sample obtained in Example 1 show that its thickness direction structure is continuous, and no obvious delamination is observed between the outer roughened area and the copper substrate; Figure 16 D1 to D18 in the figure are height markings of the local roughening protrusions on the cross section, used to assist in observing the size of the protrusions, and are not used as the measurement value of surface roughness Rz; surface roughness Rz is determined according to the white light interferometer test method described in this manual.

[0090] like Figure 17 and Figure 18 As shown, the substrate surface of the sample obtained in Example 1 exhibits a relatively uniform microstructure at both low and high magnification, which can be used to assist in observing the overall morphology and local microstructure of the substrate surface.

[0091] like Figure 19 As shown, the EBSD grain size map of the sample obtained in Example 1 can be used to characterize the grain size distribution in the detection region; in this detection sample, the average equivalent circular grain diameter is approximately 0.357 μm. Figure 20 As shown, the IPF+GB+BC diagram can be used to assist in characterizing the grain orientation, grain boundaries, and contrast distribution of the detection region.

[0092] According to the test results, the average carrier peel force at room temperature in Preparation Example 1 was 0.08 N / cm, the average carrier peel force after heat treatment at 210℃ for 90 min was 0.15 N / cm, the average Rz of the exposed surface of the conductive functional layer was 1.3 μm, and the average resin bonding peel strength was 0.55 N / mm.

[0093] Preparation Example 2 The difference between this embodiment and Preparation Example 1 is that the acid copper layer 5 was deposited using pulsed electrodeposition: the peak current density was 6.0 A / dm², the duty cycle was 60%, the pulse frequency was 100 Hz, and the deposition time was 200 s. The composition and temperature of the remaining acid copper deposition solution were the same as in Preparation Example 1. This resulted in an acid copper layer 5 with a thickness of approximately 2.5 μm, and a total conductive functional layer thickness of approximately 3.1 μm. GDOES depth profiling and integral calculation of the thickness range corresponding to the acid copper layer 5 showed that the average mass fractions of Cu, Ni, and Zn in the acid copper layer 5 were 98.4%, 0.6%, and 1.0%, respectively.

[0094] The pulse interval phase is beneficial for the recovery of the diffusion layer, which can reduce local concentration polarization and make the distribution of nickel and zinc in the acid copper layer 5 more uniform. Tests showed that the average carrier peel strength at room temperature was 0.15 N / cm, and the average carrier peel strength after heat treatment at 210℃ for 90 min was 0.25 N / cm. The average Rz of the exposed surface of the conductive functional layer was 1.5 μm, and the average resin bonding peel strength was 0.55 N / mm.

[0095] Because the content of nickel and zinc in the second functional area is relatively increased, a more compatible interface can be formed between the heat-resistant and anti-oxidation layer and the conductive functional layer, which is beneficial to improving the reliability of resin bonding after hot pressing.

[0096] Preparation Example 3 The difference between this embodiment and Preparation Example 1 is that, in the first 1 / 3, middle 1 / 3, and last 1 / 3 stages of acid copper layer 5 deposition, the concentration of nickel sulfate hexahydrate in the acid copper deposition solution is controlled sequentially to 0.8 g / L, 1.2 g / L, and 1.6 g / L, and the concentration of zinc sulfate heptahydrate is controlled sequentially to 1.2 g / L, 2.0 g / L, and 2.8 g / L; the cathode current density is 3.5 A / dm², and the total deposition time is 200 s. This results in a stepwise increase in Ni and Zn content from the side closer to the alkali copper layer 4 to the side farther away from the alkali copper layer 4.

[0097] According to GDOES in-depth analysis and integral conversion over the corresponding thickness ranges, the average mass fractions of Cu, Ni, and Zn in the alkali copper layer 4 of Example 3 were 99.3%, 0.2%, and 0.5%, respectively; while the average mass fractions of Cu, Ni, and Zn in the outer region of the acid copper layer 5 were 98.5%, 0.6%, and 0.9%, respectively. This composition distribution maintains the continuity of the conductive functional layer while giving the outer region a higher Ni / Zn content.

[0098] According to the test results, the average carrier peel force at room temperature in Preparation Example 3 was 0.20 N / cm, the average carrier peel force after heat treatment at 210℃ for 90 min was 0.35 N / cm, the average Rz of the exposed surface of the conductive functional layer was 2.5 μm, and the average resin bonding peel strength was 0.55 N / mm.

[0099] The stepped increase in element distribution allows for segmented control of nickel / zinc content along the thickness direction, while maintaining the overall continuity of the conductive functional layer.

[0100] Extended Example 1 This extended embodiment, based on Preparation Example 1, adds an organic carboxylate-type interface conditioning component to the first brushing treatment solution or the first passivation treatment solution. The organic carboxylate can be selected from at least one of sodium citrate, potassium sodium tartrate, sodium gluconate, ammonium lactate, or iminodiacetic acid, and its total concentration can be 0.5 g / L to 20 g / L; a specific combination is 5 g / L sodium citrate and 2 g / L sodium gluconate. This type of component is used to complex copper, nickel, or zinc ions and improve the wetting uniformity of the treatment solution on the carrier layer 1.

[0101] Extended Example 2 In this extended embodiment, an organic sulfonate-type interface conditioning component is added to the second brush plating solution or the first passivation solution. The organic sulfonate can be selected from at least one of methanesulfonate, alkylsulfonate, alkylbenzenesulfonate, or naphthalenesulfonate, and its total concentration can be 0.05 g / L to 5 g / L; a specific example is 0.5 g / L sodium methanesulfonate or 0.05 g / L sodium dodecylbenzenesulfonate. This type of component is used to improve wetting and adsorption conditions, but its dosage should be controlled within a range that does not significantly inhibit subsequent alkali copper nucleation.

[0102] Extended Example 3 In this extended embodiment, an organophosphate salt or organophosphonate-type interface conditioning component is added to the treatment solution forming the release layer 2 or the first passivation layer 3. The component can be selected from at least one of alkyl phosphate salts, sodium hydroxyethylidene diphosphonate, or aminotrimethylene phosphonate, and its total concentration can be 0.1 g / L to 5 g / L; a specific example is 0.5 g / L of disodium hydroxyethylidene diphosphonate. This type of component is used to complex metal ions and regulate the interfacial adsorption and passivation state.

[0103] Extended Example 4 In this extended embodiment, a nitrogen-containing organic salt or a quaternary ammonium salt-type interface modifier is added to the first passivation treatment solution. The nitrogen-containing organic salt can be selected from at least one of imidazole salts, triazole salts, benzotriazole salts, or pyridine salts, with a concentration of 0.01 g / L to 1.0 g / L; the quaternary ammonium salt can be selected from at least one of tetramethylammonium salt, hexadecyltrimethylammonium salt, or benzyltrimethylammonium salt, with a concentration of 0.005 g / L to 0.2 g / L. A specific example is 0.05 g / L of sodium benzotriazole.

[0104] The aforementioned organic salt-type interface conditioning components can be in the form of sodium salts, potassium salts, ammonium salts, or organic amine salts, and can be incorporated into one or more steps of the first brush coating treatment, the second brush plating treatment, or the first passivation treatment. To avoid the organic adsorption layer being too thick and affecting the initial deposition of the alkali copper layer 4, the total concentration of organic salts can be controlled between 0.01 g / L and 20 g / L, and the appropriate dosage can be determined through water washing, contact angle observation, initial deposition continuity, and residue after peeling.

[0105] Comparative Example 1 Using the same carrier layer 1, release layer 2, and first passivation layer 3 as in Preparation Example 1, but omitting the alkaline copper deposition step, an acidic copper sulfate deposition solution without additional nickel and zinc salts was directly used. Deposition was carried out at 4.0 A / dm² for approximately 215 s to form an extremely thin copper-based layer with a thickness of approximately 3.0 μm (the measured average mass fractions of Cu, Ni, and Zn were 99.8%, 0.1%, and 0.1%, respectively). Subsequently, a low-profile roughening layer 6, a curing treatment layer 7, a second passivation layer 8, and a silane layer 9 were formed according to Preparation Example 1.

[0106] Table 3 shows that the peel strength of the carrier at room temperature and after heat treatment at 210℃ for 90 min in Comparative Example 1 are both higher than those in Preparation Example 1, indicating that omitting the first functional region of alkali copper worsens the peel performance of the carrier side interface. The resin bonding peel strength of Comparative Example 1 is higher than that of Preparation Example 1, and existing data do not support the conclusion that its resin bonding strength is weaker than that of Preparation Example 1. This application has not conducted quantitative tests on heat oxidation resistance and fine circuit defect rate, therefore no comparative conclusions are drawn based on these.

[0107] Comparative Example 2 The same carrier layer 1, release layer 2, and first passivation layer 3 as in Example 1 were used, but a uniform Cu-Ni-Zn alloy layer of approximately 3.0 μm was continuously deposited using a single acidic deposition solution. The concentrations of nickel sulfate hexahydrate and zinc sulfate heptahydrate in the deposition solution were maintained at 1.2 g / L and 2.0 g / L, respectively, and no compositional partitioning was set between the alkali copper layer 4 and the acid copper layer 5; the average mass fractions of Cu, Ni, and Zn in the formed alloy layer could be controlled to be 98.8%, 0.5%, and 0.7%, respectively.

[0108] Table 3 shows that the peel strength of the carrier at room temperature and after heat treatment at 210℃ for 90 min in Comparative Example 2 are both higher than those in Preparation Example 1, indicating that when nickel and zinc are uniformly distributed to the side near the release layer 2, the peel performance of the carrier side interface deteriorates. The resin bonding peel strength of Comparative Example 2 is higher than that of Preparation Example 1, and existing data do not support the conclusion that its resin bonding strength is weaker than that of Preparation Example 1; this application has not conducted quantitative tests on etching rate and fine line defect rate, therefore no comparative conclusions are drawn based on these.

[0109] Comparative Example 3 The same carrier layer 1, release layer 2, first passivation layer 3, alkali copper layer 4 and acid copper layer 5 as in Preparation Example 1 are used, but the low profile roughening layer 6, curing treatment layer 7 and second passivation layer 8 are omitted, and the acid copper layer 5 is directly treated with an aqueous solution of aminosilane coupling agent with a mass fraction of 0.5% to form silane layer 9.

[0110] Table 3 shows that, after omitting the low-profile roughening layer 6, the curing treatment layer 7, and the second passivation layer 8, the resin bonding peel strength of Comparative Example 3 is lower than that of Preparation Example 1, indicating that the above surface treatment layers help improve the resin bonding performance. The carrier peel strength of Comparative Example 3 at room temperature and after heat treatment at 210℃ for 90 min are both higher than those of Preparation Example 1; however, this application has not conducted quantitative tests on heat oxidation resistance, therefore no comparative conclusions are drawn based on this.

[0111] The main differences between the examples and the comparative examples can be found in Table 1.

[0112] Table 1. Main differences between the preparation examples and the comparative examples

[0113] The performance of the preparation examples and comparative examples was evaluated using the following method. Unless otherwise specified, at least three parallel samples were selected for each group of samples, and the average value was used as the evaluation result.

[0114] (1) Carrier peel force: The carrier copper foil and the epoxy resin insulating substrate with a thickness of 0.10 mm were hot-pressed at 180℃ and 2.0 MPa for 60 min. After cooling to room temperature, the carrier peel force between carrier layer 1 and conductive functional layer at room temperature was tested by peeling at 90° and 50 mm / min. The hot-pressed sample was then heat-treated at 210℃ for 90 min. After cooling to room temperature, the carrier peel force after heat treatment was tested in the same way.

[0115] (2) Surface profile: After peeling off the carrier layer 1, at least 5 non-overlapping regions are selected at equal intervals in the transverse direction of the sample using a white light interferometer, and the Rz of the exposed surface of the conductive functional layer is measured. The evaluation length of each region is not less than 1 mm, and the measurement is performed under the same filtering and cutoff wavelength conditions. The arithmetic mean of the measured values ​​of each region is used as the result.

[0116] (3) Resin pressure peel strength: The silane layer 9 and the epoxy resin insulating substrate were hot-pressed at 180°C and 2.0MPa for 60min. After peeling off the carrier layer 1, the conductive functional layer was patterned into a 10mm wide test strip. The peel strength between the conductive functional layer and the resin substrate was tested at 90° peeling mode and 50mm / min speed.

[0117] (4) Composition in the thickness direction: GDOES was used to perform depth analysis from the side of the release layer 2 to the outside of the acid copper layer 5; the first stage deposition thickness interval corresponding to the alkali copper layer 4 and the second stage deposition thickness interval corresponding to the acid copper layer 5 were integrated respectively, and the average mass fractions of Cu, Ni and Zn were calculated based on the calibration results of the standard sample. The average EBSD equivalent circular grain diameter of the CCF18+3μm sample obtained in Example 1 was approximately 0.357μm, which can be used as a reference for the measured grain structure of copper foil.

[0118] (5) Result judgment: Preparation Examples 1 to 3 all achieved a conductive functional layer exposed surface Rz of no more than 2.5 μm, a resin pressing peel strength of no less than 0.55 N / mm, and a relatively low carrier peel force after room temperature and heat treatment. This reflects the comprehensive balance between carrier peel performance, low profile and resin bonding performance, rather than each individual performance being better than all comparative examples.

[0119] Table 2. Preparation Examples and Comparative Examples: Layer Thickness and Composition Data

[0120] Table 3. Performance data of preparation examples and comparative examples

[0121] The implementation paths of various technological advancements can be understood as follows: First, the first functional region of alkali copper is enriched with copper and serves as a transition zone between the release layer 2 and the acidic copper deposition environment, enabling the conductive functional layer to be continuously deposited on the release layer 2 and avoiding direct disturbance of the release side interface by the acidic plating solution; Second, the second functional region of acidic copper undertakes the function of thickening the conductive layer and provides a more stable outer interface foundation for the heat-resistant and anti-oxidation layer and the silane layer 9 through the relative enrichment of nickel / zinc; Third, the low-profile roughening layer 6, the curing treatment layer 7, the second passivation layer 8, and the silane layer 9 together improve the heat resistance, anti-oxidation, and interface bonding reliability of the resin bonding side.

[0122] Based on the aforementioned natural laws and mechanisms of action, the technical effect of this application is achieved by the structural and interfacial chemical relationships between the "copper enrichment first functional zone", the "nickel / zinc enrichment second functional zone", the "anti-oxidation / passivation interface on the peeling layer side", the "heat-resistant anti-oxidation layer" and the "silane layer 9", rather than solely by relying on surface roughening to form mechanical interlocking.

[0123] It is understood that this application is not limited to the detailed structure and arrangement of the proposed components. This application may have other embodiments and can be implemented and executed in various ways. The aforementioned variations and modifications are all within the scope of the protection concept of this application.

Claims

1. A low-profile carrier copper foil, characterized in that, The system includes a carrier layer and, sequentially disposed along either the rough or smooth side of the carrier layer, a first passivation layer, an alkali copper layer, an acid copper layer, a low-profile roughening layer, a curing layer, a second passivation layer, and a silane layer. The alkali copper layer constitutes a first functional region of the conductive functional layer, and the acid copper layer constitutes a second functional region of the conductive functional layer. The conductive functional layer is a copper alloy layer primarily composed of copper and containing nickel and zinc. The average mass percentage of copper in the first functional region is higher than the average mass percentage of copper in the second functional region, and the sum of the average mass percentages of nickel and zinc in the second functional region is higher than the sum of the average mass percentages of nickel and zinc in the first functional region. The low-profile roughening layer, the curing layer, and the second passivation layer together constitute a heat-resistant and oxidation-resistant layer disposed between the conductive functional layer and the silane layer. The surface roughness Rz exposed after the carrier layer is peeled off is no greater than 3.0 μm.

2. The low-profile carrier copper foil according to claim 1, characterized in that, The thickness of the conductive functional layer is 1.5 μm to 8 μm.

3. The low-profile carrier copper foil according to claim 2, characterized in that, The thickness of the first functional area accounts for 19% to 80% of the thickness of the conductive functional layer, the thickness of the second functional area accounts for 20% to 81% of the thickness of the conductive functional layer, and the sum of the thickness percentages of the first functional area and the second functional area is 100%.

4. The low-profile carrier copper foil according to claim 3, characterized in that, The average mass percentage of copper in the first functional area is 90% to 99.9%, the average mass percentage of copper in the second functional area is 80% to 99.5%, and the sum of the average mass percentages of nickel and zinc in the second functional area is more than 1.2 times the sum of the average mass percentages of nickel and zinc in the first functional area.

5. The low-profile carrier copper foil according to claim 4, characterized in that, In the conductive functional layer, the content of at least one element, nickel and zinc, increases in a stepwise manner from the side closer to the first passivation layer to the side closer to the low profile roughening layer.

6. The low-profile carrier copper foil according to claim 1, characterized in that, The second functional area is in direct contact with the low-profile roughening layer.

7. The low-profile carrier copper foil according to claim 1, characterized in that, The stripping layer includes a first stripping sublayer and a second stripping sublayer. The first stripping sublayer is formed by hypophosphite treatment, and the second stripping sublayer is formed on the side of the first stripping sublayer away from the carrier layer. The second stripping sublayer contains phosphorus and at least one metallic element selected from nickel, zinc, chromium, iron, molybdenum, cobalt, and tungsten.

8. The low-profile carrier copper foil according to claim 1, characterized in that, The low-profile carrier copper foil satisfies at least one of the following: the surface roughness Rz of the silane layer on the side away from the carrier layer is 0.3 μm to 3.0 μm; the surface roughness Rz of the conductive functional layer exposed after peeling off the carrier layer is 0.3 μm to 3.0 μm.

9. A method for preparing a low-profile carrier copper foil, characterized in that, The method for preparing the low-profile carrier copper foil according to any one of claims 1 to 8 comprises: Provides a carrier layer with a textured side and a smooth side; A release layer is formed on the rough or smooth side of the carrier layer; A first passivation layer is formed on the side of the peeling layer away from the carrier layer; An alkaline copper deposition system is used to perform a first-stage electrodeposition on the side of the first passivation layer away from the carrier layer to form an alkaline copper layer and the first functional region. A second-stage electrodeposition is performed on the side of the alkali copper layer away from the carrier layer using an acidic copper deposition system to form an acidic copper layer and the second functional region, so that the alkali copper layer and the acidic copper layer together constitute the conductive functional layer; the average mass percentage content of copper in the first functional region is higher than the average mass percentage content of copper in the second functional region, and the sum of the average mass percentage contents of nickel and zinc in the second functional region is higher than the sum of the average mass percentage contents of nickel and zinc in the first functional region; A low-profile roughening layer, a curing layer, and a second passivation layer are sequentially formed on the side of the acid copper layer away from the carrier layer. A silane layer is formed on the side of the second passivation layer away from the carrier layer.

10. The method for preparing low-profile carrier copper foil according to claim 9, characterized in that, When forming the first functional area, an alkaline copper deposition solution containing a copper complex system is used, wherein at least one of the alkaline copper deposition solution and the passivation treatment solution used to form the first passivation layer contains an organic salt-type interface conditioning component. When forming the second functional region, an acidic copper deposition solution is used, wherein the total concentration of nickel and zinc ions in the acidic copper deposition solution is increased relative to the alkaline copper deposition solution, or at least one of the current density, pulse parameters, or temperature of the second stage electrodeposition is adjusted so that the sum of the average mass percentages of nickel and zinc in the second functional region is higher than the sum of the average mass percentages of nickel and zinc in the first functional region.

11. The method for preparing low-profile carrier copper foil according to claim 9, characterized in that, The release layer includes a first release sub-layer and a second release sub-layer; the steps of forming the release layer include: performing a first brush coating treatment on the rough side or smooth side of the carrier layer using hypophosphite to form the first release sub-layer; performing a second brush plating treatment on the side of the first release sub-layer away from the carrier layer using a second brush plating solution containing metal ions to form the second release sub-layer; and performing a passivation treatment on the side of the second release sub-layer away from the carrier layer to form the first passivation layer.

12. The method for preparing low-profile carrier copper foil according to claim 9, characterized in that, During the deposition thickness increase process in the same deposition area, the supply of nickel and zinc ions, current density, or pulse parameters in the electrodeposition solution used in the second stage of electrodeposition are adjusted in stages, so that the content of at least one element in nickel and zinc in the conductive functional layer increases stepwise from the side closer to the first passivation layer to the side closer to the low profile roughening layer.